Transport of the β-lactam antibiotic benzylpenicillin and the dipeptide glycylsarcosine by brain capillary endothelial cells in vitro - Török, Michael; Huwyler, Jörg; Drewe, Jürgen; Gutmann, Heike; Fricker, Gert (Drug metabolism and disposition, 1998)
Peripherally administered β-lactam antibiotics, which are structural analogs of tripeptides, may cause neurotoxic reactions or induce seizures. Previous in vivo studies provided evidence for brain uptake of these antibiotics. In the present work, we studied the extent and mechanism of the uptake of benzylpenicillin and glycylsarcosine by brain microvessel endothelial cells in vitro, using freshly isolated and cultured porcine brain capillary endothelial cells. Characterization of the cell culture model demonstrated the functional expression of the system transporting the neutral amino acids leucine and phenylalanine. The initial rate of uptake of benzylpenicillin was >3-fold greater than the rate of uptake of the extracellular marker sucrose (ratio, 3.29 ± 0.37), whereas uptake of glycylsarcosine did not differ from that of sucrose. The differences in cellular uptake correlated with the octanol/buffer partition coefficients for glycylsarcosine and benzylpenicillin (1.16 × 10−3 for glycylsarcosine and 6.83 × 10−2 for benzylpenicillin). The concentration-dependent uptake of benzylpenicillin (1-2000 μM) was not saturable and was not sensitive to shifts in pH or temperature. The permeability-surface area product for the uptake of benzylpenicillin at pH 7.4 was determined from these experiments and was found to be 8.1 × 10−5 ml/sec/g of brain. This value was very close to the value determined in in vivo studies. Uptake of benzylpenicillin and glycylsarcosine was not reduced in the presence of 1 mM ceftibuten or 100 μM probenecid. The findings with cultured cell monolayers were confirmed using freshly isolated endothelial cells. These in vitro data are compatible with benzylpenicillin, but not glycylsarcosine, being able to penetrate endothelial cells. Uptake of benzylpenicillin by brain capillary endothelial cells occurs by a slow nonsaturable process, with no evidence for carrier-mediated transport.